Post-depositional effects on the microstructure and stable isotopes composition of planktic foraminiferal tests from the Miocene of the Pelotas Basin, south Brazilian continental margin - Geise de Santana de Santana dos Anjos-Zerfass; Farid Chemale Jr.; Candido A. V. Moura (Revista Mexicana de Ciencias Geológicas)
An integrated study of planktic foraminiferal tests (Orbulina universa and Globigerinoides trilobus) imaging techniques and chemical/isotopic analyses has been carried out at the Miocene section of the Pelotas Basin (South Brazil) with the purpose of record and evaluate the effects of the diagenesis in its wall texture and isotopic composition. The characterization of the foraminiferal tests preservation prior performing isotopic analysis for paleoceanographic studies is essential to ensure the choice of suitable material for obtaining reliable data. Scanning electron microscopy, backscatter scanning electron microscopy, energy-dispersive X-ray spectrometry and stable isotope measurements were used to evaluate the post-depositional effects on the tests. It was possible to identify features of dissolution, neomorphism (recrystallization) and coating of autigenic minerals. The stable isotopic data define two compositional groups. The heavier and less scattered values characterize a preserved paleoenvironmental signal as the lighter and scattered ones indicate a signal derived from post-depositional alterations. Additionally, the characterization of the distinct types of diagenetic changes and their textural products provide a guideline for the evaluation of the diagenetic effects of deeply buried fossil foraminifera.